2019
DOI: 10.1016/j.atherosclerosis.2019.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Ideal cardiovascular health and risk of acute myocardial infarction among Finnish men

Abstract: This is a self-archived version of an original article. This version may differ from the original in pagination and typographic details.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…A trained research nurse was responsible for interviewing all the study participants, who also went through a health examination. Details of the assessment for the blood pressure (BP), BMI, nutritional status, smoking status, alcohol consumption, physical activity, prevalent medical conditions and socioeconomic status (SES) have previously been discussed 6 . The SES scale ranges from 0 through 25; 0 indicating the highest, and 25 the lowest SES.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…A trained research nurse was responsible for interviewing all the study participants, who also went through a health examination. Details of the assessment for the blood pressure (BP), BMI, nutritional status, smoking status, alcohol consumption, physical activity, prevalent medical conditions and socioeconomic status (SES) have previously been discussed 6 . The SES scale ranges from 0 through 25; 0 indicating the highest, and 25 the lowest SES.…”
Section: Data Collectionmentioning
confidence: 99%
“…The CVH metrics adopted in this study was in conformity with the CVH metrics developed by AHA, consisting of 7 health behavioural and biological factors including healthy diet score (HDS), physical activity, BMI, smoking status, BP, fasting blood glucose and plasma total cholesterol 3,6 (Supplementary Table 1). Thus, the ideal CVH metric consists of: 1) HDS of 4 -5, i.e.…”
Section: Cardiovascular Health Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiovascular diseases have long been causing deaths to the largest number of humans. Acute Myocardial Infarction (AMI), one of the world's most common major cardiovascular diseases is characterized by high mortality and disability [1,2]. Despite the significant progress made in the treatment of AMI in recent years, its mortality rate remains relatively high [3].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that changing poor behaviors and metabolic factors can reduce dyslipidemia as effectively as clinical drug therapy [9] . However, although healthy behaviors and metabolic factors were negatively correlated with the disease risk [10,11] , but the proportions of healthy behaviors and metabolic factors that meet the ideal levels were extremely low [12] .…”
mentioning
confidence: 96%